1095 Use of Amplitude Integrated Electroencephalography in Newborns with Severe Hyperbilirubinemia. (October 2012) - Chang, M; Shin, JH
Abstract : Background and Aims: The spectrum of bilirubin-induced neurologic dysfunction (BIND) is very wide and the symptoms and signs may be very mild or absent. Amplitude-integrated electroencephalography (aEEG) allows continuous trend recording of cerebral function in high-risk newborns. However, published knowledge regarding correlation between aEEG and BIND remains limited. In this study, we hypothesized that abnormal aEEG in infants with severe hyperbilirubinemia is useful for detection of asymptomatic BIND. Methods: This is a prospective observational study of newborns with severe hyperbilirubinemia in our NICU from April 2011 to December 2011. Patients were included if they were ≥ 34 weeks gestational age (GA) at birth and their total serum bilirubin [TSB] >20 mg/dL. The aEEG was performed for 6 hours since admission, and rechecked when TSB is below 10 mg/dL. Results: Fourteen infants were enrolled. Male to female was 10 to 4. Their GA was 37.2±1.2 weeks and their birth weight was 3, 238±421 g. Their peak TSB was 23.63±2.7 mg/dL. Photopherapies were performed in all infants and exchange transfusions were also performed in 2 infants. Six out of 14 infants (42.8%) showed abnormal aEEG findings such as discontinuity, abnormal cycling, depressed lower border and abnormal bandwidth span when their TSB were markedly elevated. However none had any noticeable symptoms or signs of neurologic dysfunction. All abnormal aEEG findings were normalized after treatment. Conclusions: Abnormal aEEG finding in infants with severe hyperbilirubinemia is useful for detection of asymptomatic BIND and can be reversible with appropriate treatment.